Topological transitivity of translation operators in a non-separable Hilbert space - Z.H. Novosad (Karpatsʹkì Matematičnì Publìkacìï, 2023)
We consider a Hilbert space of entire analytic functions on a non-separable Hilbert space, associated with a non-separable Fock space. We show that under some conditions operators, like the differentiation operators and translation operators, are topologically transitive in this space.